2015
DOI: 10.4314/gjgs.v13i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry and quality assessment of some ground water samples from Enugu and environs, south-eastern, Nigeria

Abstract: This study was carried out to evaluate the groundwater quality and its suitability for drinking purposes in Enugu and environs, southeastern Nigeria. Water samples for this study were collected from ten different locations within the study area. Nine of the samples were subjected to physico-chemical analyses only, two out of the nine were subjected to both physico-chemical and microbiological analyses, while one (Egede borehole) was subjected to microbiological analyses only. The minimum and maximum values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Silica analysis in Nando and Udi by Egbunike [53] and Aniebone [128] , showed that it ranged from <0.001 to 30 mg/l (Figure 18). Silica is the most plentiful element found in rocks and it is constantly present in natural waters [129][130][131] .…”
Section: Cation Chemistrymentioning
confidence: 99%
“…Silica analysis in Nando and Udi by Egbunike [53] and Aniebone [128] , showed that it ranged from <0.001 to 30 mg/l (Figure 18). Silica is the most plentiful element found in rocks and it is constantly present in natural waters [129][130][131] .…”
Section: Cation Chemistrymentioning
confidence: 99%
“…Therefore, application of inverse modelling to Ekulu river will give insight to the evolution and pollution sources. Previous researches reveal that Ekulu river and other rivers in Enugu are highly contaminated (Osuinde and Eneuzie, 1999;Aniebone, 2014;Ugochukwu et. al, 2019;Chinedu et al, 2021;Ken-Onukuba et.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this stream is used as a -natural lavatory‖, as evidenced by high deposits of human excrement along the river banks in Abakpa area. Aniebone (2014) carried out research to determine the bacterial contaminant in surface water around Enugu metropolis, and found high concentrations of heavy metals and pathogens with colonies ranging between 10 to over 200. High coliform count in Ekulu River may be an indication that the water sources were faecal contamination (Osuinde and Eneuzie, 1999).…”
Section: Introductionmentioning
confidence: 99%